(untitled) (GIST – Education and Learning Research Journal, 2021)
The main objective of this study is to explore various barriers that are preventing Pakistani HEIs (universities) students from learning online in this COVID-19 pandemic. Applying a qualitative research design, twelve (12) in-depth interviews were conducted with individual business school participants (students), selected at undergraduate and graduate levels to participate. Data were collected from six (06) universities in Islamabad, Pakistan. After collecting the data using a self-developed questionnaire, a thematic analysis method within the qualitative research was applied to uncover several barriers relating to the objective of this study. Eight themes emerged from the interview data: internet technology access, the content of digital slides, student’s perception towards online learning, power outages during COVID-19 pandemic, students’ fear of losing marks and impact on employment, faculty skills in using technology to teach online, student’s stress and health in the COVID-19 pandemic and student skills to use distance learning tools. Based on the findings, students who live in rural areas are more affected by online learning during the COVID-19 pandemic than students in urban areas due to identified barriers and, most importantly, lack of technology infrastructure. Opportunities and future recommendations have been provided to the relevant authorities to conduct and deliver smooth online education in the country during pandemic.